The larvae of Diadema setosum (Leske, 1778) (Camarodonta: Diadematidae) from South China Sea. Issue 4 (1st October 2016) - Dautov, S. S.; Dautova, T. N.
Abstract: Diadema setosum (Leske, 1778) develops from small isolecithal eggs with a diameter of 84 ± 3 μm. Embryonic development took about 6.5–7 h and finished when a blastula left the fertilization envelope and became a larva. At this stage, the first pigment cells had appeared. At 23 h a prism developed; at 44 h a pluteus with one pair of arms had appeared; at 45 h of development plutei had two pairs of arms. The pigment cells colour the pluteus of D. setosum dark red. When 20-day-old larvae were mechanically stimulated, they flared their arms which may be defensive behaviour. During further development, the post oral arms of plutei grew to 1900 μm or more. Metamorphosis took place at about 40–45 days. At this time, five primary ambulacral podia were visible within the larval body. The duration of metamorphosis from the moment of larval settlement until the juvenile sea urchins began to move along the bottom was 40–60 min. The diameter of the test of the newly metamorphosed juvenile sea urchins was about 500 μm.